A comparison of the impact of the Basel standards upon Islamic and conventional bank risks in the Gulf state region. Issue 2 (4th March 2019) - Farooqi, Muhammad Fuad; O'Brien, John
Abstract : Purpose: This paper aims to provide a comparative study of the Islamic versus conventional banking sector risk by using market data generated from the sample of publicly listed Islamic and conventional banks in the Gulf Cooperation Council (GCC) region. Design/methodology/approach: The authors introduce a market-based measure of bank stress and test this indicator against the Tier 1 Capital Ratio using Granger causality tests. Findings: The authors find that the market-based measure is a leading indicator of banking stress when compared to the accounting-based Tier 1 ratio and thus is relevant to the Basel regulation's Pillar 3. Research limitations/implications: This paper only looks at Islamic vs conventional banks in the Gulf region, and the authors would like to extend this analysis to a broader range of financial institutions, especially in the European and North American markets. Social implications: Developing a measure that signals bank stress ahead of typically used measures can help regulators, bank management and investors identify oncoming problems and issues before these become too big to manage. Originality/value: The results from this analysis provides insight into the offsetting impact from two drivers (beta and book-to-market ratio) of the cost of equity capital for the conventional vs Islamic banking sectors.